The Effect of Environmental Performance and Leverage on Financial Performance - dahlan, muhammad (IJRDO - Journal of Business Management, 2023)
Purpose: This study aims to determine the effect of environmental performance and leverage on financial performance.Method: The approach used in this research is quantitative method. This study uses secondary data from annual reports of manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2021 period, amounted to 46 samples. The analysis technique used is multiple linear regression.Results: The result indicates that environmental performance has a positive and significant effect on financial performance and leverage has a negative and significant effect on financial performance.Limitations: This study’s limitations are the short research period from 2020-2021 and only use two variables as the independent variables.Contribution: The results obtained can be used as an evaluation material for the company and provide insight for investors in making investment decisions. This study can also be used as a reference for further research.